2022
DOI: 10.1002/cam4.5499
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of in silico analysis estimated the reverse effect of upregulated hsa‐miR‐106a‐5p and hsa‐miR‐223‐3p on SLC4A4 gene expression in Iranian patients with colorectal adenocarcinoma by RT‐qPCR

Abstract: Background and Methods Colorectal cancer (CRC) is considered one of the most common malignancies worldwide. The diagnosis and prognosis of the patients are very poor. In this study, we used in‐silico analysis and experimental techniques to investigate novel co‐expression genes and their associated miRNA networks in CRC. For this purpose, we conducted a comprehensive transcriptome analysis using online bulk and single‐cell RNA‐seq datasets. We then validated the results on tissue samples from cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…By contrast, hsa-miR-223-3p is already recognized as upregulated in both serum from UC and biopsies from CRC patients [ 26 , 27 ]. Finally, hsa-miR-331-3p appeared to protect against neuronal-related inflammation, although other studies reported that an inhibition of this miRNA could ameliorate Alzheimer’s disease [ 28 , 29 , 30 ]. Interestingly, hsa-let-7d-5p, hsa-miR-223-3p, hsa-miR-145-5p, and hsa-miR-16-5p all regulated ACVR2A mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, hsa-miR-223-3p is already recognized as upregulated in both serum from UC and biopsies from CRC patients [ 26 , 27 ]. Finally, hsa-miR-331-3p appeared to protect against neuronal-related inflammation, although other studies reported that an inhibition of this miRNA could ameliorate Alzheimer’s disease [ 28 , 29 , 30 ]. Interestingly, hsa-let-7d-5p, hsa-miR-223-3p, hsa-miR-145-5p, and hsa-miR-16-5p all regulated ACVR2A mRNA.…”
Section: Discussionmentioning
confidence: 99%